2017
DOI: 10.1007/978-3-319-59250-3_25
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Polynomial Approximation for the Restricted Assignment Problem

Abstract: Scheduling jobs on unrelated machines and minimizing the makespan is a classical problem in combinatorial optimization. In this problem a job j has a processing time pij for every machine i. The best polynomial algorithm known goes back to Lenstra et al. and has an approximation ratio of 2. In this paper we study the Restricted Assignment problem, which is the special case where pij ∈ {pj , ∞}. We present an algorithm for this problem with an approximation ratio of 11/6 + ǫ and quasi-polynomial running time n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…While the additive integrality gap of the assignment-LP can be as large as p max , this gap is only ǫ • p max for the slot-MILP. We show this using a rounding procedure inspired by a local search method for the restricted assignment problem [28,18,19]. The local search algorithm repeatedly moves jobs between machines, eventually converging to a good solution.…”
Section: Introductionmentioning
confidence: 99%
“…While the additive integrality gap of the assignment-LP can be as large as p max , this gap is only ǫ • p max for the slot-MILP. We show this using a rounding procedure inspired by a local search method for the restricted assignment problem [28,18,19]. The local search algorithm repeatedly moves jobs between machines, eventually converging to a good solution.…”
Section: Introductionmentioning
confidence: 99%
“…Again, our FPTAS has a better dependence on m and ∆ 1 , than an exact algorithm from [3]. Additionally, it gives a better dependence on ∆ 1 , than an exact algorithm from [9].…”
Section: Description Of the Results And Related Workmentioning
confidence: 81%
“…Additionally, we need to note that better complexity bound for searching of an exact solution can be achieved for the unbounded version of the mdimensional knapsack problem. More precisely, for this case the paper [9] gives the complexity bound…”
Section: Description Of the Results And Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a breakthrough result, Svensson [36] showed that a certain integer linear program modeling the problem has an integrality gap of at most 33/17, which implies an algorithm approximating the optimal objective value with rate 33/17+ε for any ε > 0 without producing a corresponding schedule. This has been improved by Jansen and Rohwedder [18] to a rate of 11/6, and in [19] the same authors provide a quasi-polynomial approximation algorithm with rate 11/6 + ε that also outputs a corresponding schedule. For the special case of restricted assignment with only two distinct processing times (not counting ∞) an approximation algorithm due to Chakrabarty, Khanna and Li [4] with a rate slightly below 2 is known.…”
Section: Introductionmentioning
confidence: 99%